Improved Ability to Deliver Negotiated Texts Through Articulation Learning Model - Imansudi Zega; Aprianus Zega; Noveri Amal Jaya Harefa (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to improve the ability of the class X MIPA-I SMA Negeri 2 Gunungsitoli even semester consisting of 36 people to convey negotiating texts through the Articulation learning model. To achieve this goal, the researchers carried out Classroom Action Research with the implementation procedures were (1) planning, (2) action, (3) observation, (4) reflection. The results of data analysis from the knowledge test in the first cycle reached an average value of 61.33 with the lowest score 52 and the highest 72. The knowledge value in the second cycle reached an average value of 84.33 with the lowest score 72 and the highest score 96. The results of analysis of student activity observation data in the first cycle of the first meeting with an average of 46.79% and the second meeting 52.35% (predicate